2017
DOI: 10.1039/c7tb00657h
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable nanocomposites with bone-like strength and enhanced cellular activity

Abstract: Bone cements for treatment of fractures at weight-bearing sites are subjected to dynamic physiological loading from daily activities. An ideal bone cement rapidly sets after injection, exhibits bone-like strength, stimulates osteogenic differentiation of endogenous cells, and resorbs at a rate aligned with patient biology. However, currently available materials fall short of these targeted properties. Nanocrystalline hydroxyapatite (nHA) enhances osteogenic differentiation, new bone formation, and osteoclast d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 70 publications
2
35
0
Order By: Relevance
“…[27, 28] In a recent study, lysine triisocyanate (LTI) was grafted to nanocrystalline hydroxyapatite (nHA) particles and crosslinked with poly(ε-caprolactone) triol to create nHA-PEUR hybrid inorganic-organic polymers with bending and compressive strengths >90 MPa, which is sufficiently high to support structural repair of bone. [29] nHA-PEUR stimulated osteoid mineralization and exhibited osteoclast-mediated resorption in vitro [29] and in vivo . [30] These nHA-PEUR hybrid polymers are resistant to hydrolytic degradation (<2% mass loss after 4 months at 37¼C in vitro )[31, 32] but readily degrade in the presence of reactive oxygen species (ROS) secreted by infiltrating cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27, 28] In a recent study, lysine triisocyanate (LTI) was grafted to nanocrystalline hydroxyapatite (nHA) particles and crosslinked with poly(ε-caprolactone) triol to create nHA-PEUR hybrid inorganic-organic polymers with bending and compressive strengths >90 MPa, which is sufficiently high to support structural repair of bone. [29] nHA-PEUR stimulated osteoid mineralization and exhibited osteoclast-mediated resorption in vitro [29] and in vivo . [30] These nHA-PEUR hybrid polymers are resistant to hydrolytic degradation (<2% mass loss after 4 months at 37¼C in vitro )[31, 32] but readily degrade in the presence of reactive oxygen species (ROS) secreted by infiltrating cells.…”
Section: Introductionmentioning
confidence: 99%
“…[29] nHA-PEUR stimulated osteoid mineralization and exhibited osteoclast-mediated resorption in vitro [29] and in vivo . [30] These nHA-PEUR hybrid polymers are resistant to hydrolytic degradation (<2% mass loss after 4 months at 37¼C in vitro )[31, 32] but readily degrade in the presence of reactive oxygen species (ROS) secreted by infiltrating cells. [32, 33] Thus, nHA-PEUR-derived bone cements are anticipated to provide mechanical stability as they remodel, since they undergo negligible degradation until cells infiltrate the cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with pure HA of the same crystallinity, Mg-doped HA implant materials offer better adhesion and proliferation of osteoblast cells [36]. Therefore, a HA surface can layer presents superior osteoconductivity, can promote cellular function, and offers excellent biocompatibility [47,48]. The apatite layer deposited on the biocomposite pins investigated in this study had a lower Ca/P ratio than the stoichiometric HA (1.67) (Figure 5A,B), whereas the Ca/P ratio of the apatite layer deposited on the pure PLDLA was 1.82 (Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a templating approach in which 3D‐printed wax molds were filled with a reactive, flowable, and settable poly(ester urethane)‐nanocrystalline hydroxyapatite (PUR‐nHA) hybrid polymer with bone‐like strength. We have shown that this organic–inorganic hybrid polymer promotes osteoblast differentiation and mineralization, supports osteoclast‐mediated resorption, and remodels to form new bone in vivo …”
mentioning
confidence: 99%